Sikap Orang Tua dengan Kejadian Obesitas pada Anak Usia 6-12 Tahun - Mochamad Heri; Komang Gde Trisna Purwantara; Ni Made Dwi Yunica Astriani; I Dewa Ayu Rismayanti (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between parent's attitudes and the incidence of obesity in children aged 6-12 years at SD Negeri 1 Banyuasri. This type of research is descriptive correlational with a cross-sectional approach. This study indicates that 24 people (53.3%) have a positive attitude towards obesity in children aged 6-12 years with six (13.3%) obese children. Data analysis results with the Chi-Square test obtained a value of 0.000 or p<α (0.05). In conclusion, there is a significant relationship between parent's attitudes and the incidence of obesity in children aged 6-12 years at SD Negeri 1 Banyuasri. Keywords: Children 6-12 Years, Obesity, Parent’s Attitudes